Interventions for Person with Dementia: A Scooping Review - Makdum Alaidin; Suyanto Suyanto (Indonesian Journal of Global Health Research, 2026)
Dementia is a progressive neurodegenerative condition that significantly affects a person's cognitive function, behavior, and quality of life. The increasing global prevalence of dementia poses significant challenges for healthcare systems, families, and communities. Pharmacological therapies have shown limited effectiveness and are often associated with side effects, so non-pharmacological and multidimensional interventions are gaining increasing attention as more comprehensive alternative approaches. The aim of this study is to identify and map the scientific evidence regarding various interventions applied to people with dementia and to provide a conceptual basis for the development of clinical practice and further research to improve the quality of care and quality of life of individuals with dementia. Literature search was conducted in electronic databases such as PubMed, and Spingerlink using keywords related to “dementia,” and “intervention” for the period 2015-2025. Studies meeting the inclusion criteria were analyzed descriptively and categorized by intervention type: pharmacological, non-pharmacological, psychosocial, and alternative therapies. The 14.403 articles found, 18 studies met the inclusion criteria. Non-pharmacological interventions, including interventions for person with dementia in the form of cognitive stimulation, music interventions, psychosocial interventions, reminiscence therapy, aromatherapy, physical activity and exercise, and animal therapy that have been proven to person with dementia and have also been shown to strengthen social interactions and reduce caregiver stress. Pharmacological interventions have shown more limited results and focus on symptom management rather than improving overall quality of life. Interventions for persons with dementia are diverse and predominantly non-pharmacological, with growing evidence supporting their potential benefits across cognitive, psychological, and quality-of-life outcomes.